La forza degli oggetti ricomposti - Elisa Rondini; Daniele Parbuono (EtnoAntropologia)
Those implemented by Elio, who lives in Paciano (Perugia), in a farmhouse immersed in the things of his creativity, are configured as housing strategies defined and continually redefined starting from the use of heterogeneous tools and materials, collected from contingent circumstances and adapted to contextual needs. Like Levi-Strauss’s bricoleur, he combines skills, expertise and available resources (things out of everyday use, found waste collection centers and garages of relatives and friends), configuring an instrumental universe in constantly adapting his living space based on extra-ordinary and always progressive aesthetics. Elio does not buy and does not sell, but retrieves and builds, giving new trajectories to the recomposed things and new meaning to his practices, whether they are family, social, work, or existential.